Metaphors of waste: several ways of seeing "development" and Cairo's garbage collectors - Furniss, P (2012)
The struggle with garbage is not only a physical struggle to deal with the unwanted stuff people throw away. It is also a struggle over meanings. At the centre of that struggle in Cairo are the Zabbaleen: the city's 'informal sector' or 'traditional' waste collectors. Over the past 40 years the Zabbaleen have been the focus of a great deal of outside attention and intervention, especially by the Egyptian state and development organizations. Based on 1.5 years' fieldwork in Cairo, including interviewing, archival work, and analysis of artefacts of mass culture such as film and newspapers, this dissertation asks how different outsiders represented and construed the Zabbaleen, and what they wanted to change about them. Each chapter corresponds to a different outside viewpoint. Chapter 3 examines the beginning of the story of outside development intervention, with the French Mother Theresa figure Sr. Emmanuelle. Starting in 1971, she lived with the Zabbaleen and built schools, hospitals and clubs for them. Chap- ter 4 examines how a popular Egyptian film, which appeared in 1980, used the story of a garbage collector's success as a social metaphor for the country's dysfunction and the overthrow of its mod- ernist ideal. Chapter 5 examines a series of Zabbaleen development projects implemented by the World Bank (water, sewer and electricity) and its consultants (modifications to the Zabbaleen built environment and behaviour) between the late 1970s and the early 1990s. Chapter 6 discusses the Egyptian Government's decision to contract European waste management firms in the early 2000s. Chapter 7 examines why and how the Egyptian state decided to slaughter all pigs (raised by the Zab- baleen) during the 'swine flu' epidemic in 2009, and how this split Christians in the country. The ambition of the dissertation is to make a contribution to critical development studies. It plots the evolution of development thinking and practice over the forty-year period covered (including weigh- ing developmentalism relative to other paradigms of intervention), and demonstrates how interpreta- tions of waste have been central to shaping interventions and imaginaries of 'development' through- out that period.